Combined immuno‐purification and detection of recombinant erythropoietins and activin receptor type II‐Fc fusion proteins by isoelectric focusing for application in doping control. Issue 1 (28th August 2018) - Martin, Laurent; Audran, Michel; Marchand, Alexandre
Abstract: Iso‐electric focusing (IEF) was the first method established to discriminate endogenous and recombinant erythropoietins (rEPOs). It is still approved by the World Anti‐Doping Agency (WADA) as an initial testing procedure to detect erythropoiesis stimulating agents (ESAs) in doping control samples. However EPO‐Fc, one of the prohibited rEPOs designated by WADA, is not detectable with the actual IEF conditions. Other newly developed ESAs – luspatercept and sotatercept, both activin receptor type II‐Fc fusion proteins (ActRII‐Fc) – are also now prohibited and could be used in combination with rEPOs. Methods of identification of ActRII‐Fc in blood by SAR/SDS‐PAGE have been described, but not by IEF. Here we detail improvements in blood sample preparation and IEF analysis: A combined immuno‐purification of EPOs and ActRII‐Fc proteins in a single procedure, an appropriate isoforms separation for all proteins using new pre‐loading and gel conditions, and a single detection of all rEPOs and ActRII‐Fc proteins after successive incubation with anti‐EPO and anti‐ActRII antibodies. With these changes, distinctive profiles for all the ESAs were obtained by IEF. Therefore, IEF could be used as a screening method to detect a wide spectrum of prohibited ESAs in blood samples prior to specific confirmation for the identified rEPO or ActRII‐Fc.